Hazards and Control Measures among Artisanal and Small-Scale Gold Miners in Zimbabwe - Singo, Josephine; Isunju, John Bosco; Moyo, Dingani; Steckling-Muschack, Nadine; Bose-O’Reilly, Stephan; Mamuse, Antony (Ubiquity Press, 2022)
Background: In 2017 around 14–19 million miners were exposed to multiple hazards in artisanal and small-scale gold mining (ASGM). ASGM is characterized by basic and compromised mining methods with either very limited control of hazards or none at all. There is little knowledge about health and safety among artisanal and small-scale gold miners in Zimbabwe.